(untitled) (Global Journal of Science Frontier Research, 2015)
The study covered four rice terraces clusters in the Cordillera region, Northern Philippines located in Asipulo, Ifugao, Tanglagan, Apayao Province, Bagumbayan, Tabuk City, Kalinga and Natonin, Mt. Province. The study assessed the changes that has occurred in the rice terraces and their impacts on labor dynamics and food security. To obtain the necessary data, a timeline workshop was conducted for each site involving ten farmer key informant for each study site and validated by a separate group of ten farmers. The result showed that the rice terraces started mainly as a traditional type of farming system relying mainly on human labor using farming practices developed and handed down from older generations. The modern farming innovation adopted by farmers are: substitution of traditional rice varieties to high yielding rice varieties, use of commercial fertilizers and pesticides, farm mechanization with hand tractors, rice threshers and rice mills and improvement of irrigation canals. High yielding rice varieties increased yield of rice by 50% to 70% vis a vis the traditional varieties and enhanced the food security situation in the rice terraces.